Macromedia Dreamweaver 8 : interactive movie tutorials - Human, Renee; Thompson Course Technology (Boston, MA. : Thomson Course Technologies, 2006)
Movie tutorials in designing web page using Macromedia Dreamweaver 8. Includes glossary, quizzes and other information
A QuickTime for both Windows and Macintosh
Keywords: Dreamweaver (Computer file); Web sites -- Design